The Passenger: Medieval Texts and Transits - Smith, James L. (punctum books, 2017)
What strange transactions take place in the mobile spaces between loci? How does the flow of forces between fixed points enliven texts, suggest new connections, and map out the dizzying motion of myriad interactions? The essays in this volume were first presented at the 2014 New Chaucer Society Congress in Reykjavik, Iceland where a meeting of minds in a shared intermediate space initiated dialogue from diverse perspectives and wended its way through the invisible spaces between concrete categories, objects, and entities. The resulting volume asks a core question: what can we learn by tarrying at the nexus points and hubs through which things move in and out of texts, attempting to trace not the things themselves or their supposedly stable significations, but rather their forms of emergence and retreat, of disorder and disequilibrium? The answer is complex and intermediate, for we ourselves are emerging and retreating within our own systems of transit and experiencing our own disequilibrium. Scholarship, like transit, is never complete and yet never congeals into inertia.